Nilai Amar Ma’ruf Nahi Mungkar Dalam Ekonomi Islam - Yupi Pirdayanti (Journal of Islamic Economics and Bussiness Studies, 2022)
Islamic economics is a reflection of the Qur'an, which incorporates the principles of law and regulations concerning the economic problems of mankind which are sourced from the Qur'an and hadith. On the other hand, Islamic economics is not only for Muslims but also for everyone because Islam is rahmatan lil alamin. One of the important values in Islamic economics is the value of amar ma'ruf nahi munkar. The research method in this paper is a qualitative research with a descriptive method, which is included in the type of library research. The results showed that in Islam the economy must be run according to the rules of Allah SWT. So that in carrying out economic activities must always refer to the Qur'an and hadith. So to prevent violations of Islamic law in carrying out the economic system, amar ma'ruf nahi munkar activities are needed so that the wheels of the economy run according to Islamic law. Meanwhile, the activity of amar ma'ruf nahi munkar functions as a control in running the economy.